Verruciform xanthoma of the upper anterior gingiva - Rodrigues, Janderson Teixeira; Santos Netto, Juliana de Noronha; Miranda, Aguida Maria Menezes Aguiar; Amaral, Simone de Macedo; Pires, Fábio Ramôa (Journal of Oral Diagnosis, 2017)
Introduction: Verruciform xanthoma (VX) is a reactive oral mucosal lesion that can re- semble other papillary conditions. Objective: To report a case of gingival VX clinically mimicking other papillary swellings. Case report: A 66-year-old female presented for evaluation of a painless papillary growth in the gingival margin of the upper right central incisor. Clinical diagnosis included papillary gingival hyperplasia and VX. An excisional biopsy was done and histology revealed a proliferative surface epithelium with papillary projections and CD68+ xanthomatous cells on the upper papillary superficial connective tissue. Diagnosis was VX and the patient remains in clinical follow-up with no signs of recurrence for 4 months. Conclusion: VX should be considered in the differential diagnosis of gingival papillary swellings.